High school students' ability to transcribe mathematical phrases to symbols - Narciso, Nora M. (1979)
A 38-item test on mathematical phrases was used in determining the ability of first year high school students to transcribe mathematical phrases to symbols. The students tested were generally poor in transcribing mathematical phrases. The difficulty was due to language problem, reading comprehension and failure to do reflective thinking. Mental ability and reading comprehension were closely related with the students' ability to transcribe mathematical phrases. This means that a student with high mental and reading comprehension ability find less difficulty in transcribing mathematical phrases.